1982
DOI: 10.1111/j.1471-4159.1982.tb03989.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Lead Ingestion by Rats on Glucose Metabolism and Acetylcholine Synthesis in Cerebral Cortex Slices

Abstract: The effect of chronic low-level lead (Pb2+) ingestion on the metabolic pathways leading to the acetyl moiety of acetylcholine (ACh) was examined. Cerebral cortex slices, prepared from untreated or Pb2+-exposed rats (600 ppm lead acetate in the drinking water for 20 days), were incubated in Krebs-Ringer bicarbonate buffer with 10 mM glucose and tracer amounts of [6-3H]glucose and either [6-14C]glucose or [3-14C] beta-hydroxybutyrate. Altering the concentration of Pb2+ in the drinking water produced a dose-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…It is thus suggested that utilization as well as uptake of glucose were deteriorated by lead in the anterior horn of the spinal cord. This is in line of observations of the adverse effects of lead on glucose metabolism [1][2][3][4] . The anterior horn cell (spinal motor neuron) bodies have the highest values of GUR and DV in the spinal cord 5) .…”
supporting
confidence: 73%
See 1 more Smart Citation
“…It is thus suggested that utilization as well as uptake of glucose were deteriorated by lead in the anterior horn of the spinal cord. This is in line of observations of the adverse effects of lead on glucose metabolism [1][2][3][4] . The anterior horn cell (spinal motor neuron) bodies have the highest values of GUR and DV in the spinal cord 5) .…”
supporting
confidence: 73%
“…The decrease in conversion of [ ] glucose into lactate, citrate and malate was observed in cerebral cortex slices obtained from two groups of rats with mean blood lead (BPb) concentrations of 31.8 and 54.2 µg/dl, respectively, which had been given drinking water containing 200 or 600 ppm of lead for 20 days 1) . The conversion rate of [ 14 C] glucose to 14 CO 2 was reduced in brain capillaries isolated from cerebral cortex of calves with BPb of 118 ± 0.19 µg/dl, which were given 15 mg/kg bw of lead acetate orally for 7 to 8 days, showing no histopathological changes 2) .…”
mentioning
confidence: 99%
“…Although there have been many studies devoted to studying the effects of Pb exposure, the molecular mechanisms behind the subtle neurotoxic effects of lower levels of Pb remain largely unknown. However, disrupted energy metabolism is one mechanism that has been proposed as a possible cause of the behavioral abnormalities and brain dysfunction induced by Pb (Sterling et al, 1982).…”
mentioning
confidence: 99%